2022
DOI: 10.1111/all.15375
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Haemophilus influenzae infection of pulmonary macrophages drives neutrophilic inflammation in severe asthma

Abstract: Background: Nontypeable Haemophilus influenzae (NTHi) is a respiratory tract pathobiont that chronically colonizes the airways of asthma patients and is associated with severe, neutrophilic disease phenotypes. The mechanism of NTHi airway persistence is not well understood, but accumulating evidence suggests NTHi can persist within host airway immune cells such as macrophages. We hypothesized that NTHi infection of pulmonary macrophages drives neutrophilic inflammation in severe asthma. Methods: Bronchoalveola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Recent evidence suggests that IL1B expression may be driven by intracellular infection of macrophages. 47 Although all subjects in our study were free of upper respiratory tract infection within 4 weeks, whether this change in IL1B expression is a cause of EA or an effect of airway microbiome changes in EA remains to be further addressed.…”
Section: Discussionmentioning
confidence: 92%
“…Recent evidence suggests that IL1B expression may be driven by intracellular infection of macrophages. 47 Although all subjects in our study were free of upper respiratory tract infection within 4 weeks, whether this change in IL1B expression is a cause of EA or an effect of airway microbiome changes in EA remains to be further addressed.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies on sputum microbiome in asthma and COPD 9 , 32 or in severe asthma 8 , 10 , 33 showed an association between neutrophil-high phenotype and γ-proteobacteria or Haemophilus , and studies during exacerbations 27 and at stable state 9 identified a cluster mainly containing patients with COPD and some with asthma, which was characterized by an increased ratio of γ proteobacteria to Firmicutes and high IL1-β and TNF-α levels. Consistent with previous studies, relative abundances of γ Proteobacteria and Haemophilus were associated with airway neutrophilia in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Neutrophilic inflammation has been repeatedly detected in the airways where the phylum Proteobacteria, which includes class γ Proteobacteria with a large number of pathogenic Gram-negative rods such as Haemophilus spp, is the predominant flora over the phylum Firmicutes, which includes Gram-positive cocci such as Streptococcus spp. 8 , 9 , 10 In addition, steroid-naive patients with eosinophil-low asthma had more abundant genus Bacteroides in the lower airways than those with eosinophil-high asthma, 11 and operational taxonomic units of Bacteroides sp. in the gut were negatively associated with blood eosinophil percentage in patients with COPD, 12 suggesting that Bacteroides may be linked to eosinophil-low phenotype.…”
mentioning
confidence: 99%
“…Besides these possibilities, NTHi may evade immune clearance via other additional mechanisms. NTHi is phagocytosed by airway macrophages, and has been observed within bronchoalveolar macrophages in asthma using FISH ( Ackland et al., 2022 ), whilst in monocyte derived macrophages phagocytosed NTHi remains stably viable at 24 h post infection ( Ackland et al., 2021 ). Furthermore, although NTHi does not produce extracellular polysaccharides required for classic biofilm formation ( Moxon et al., 2008 ), it is protein and DNA rich ( Gunn et al, 2016 ), and may persist extracellularly within biofilm-like structures formed from neutrophil breakdown products ( Langereis and Hermans, 2013 ).…”
Section: Discussionmentioning
confidence: 99%